Stem-cell Based Engineered Immunity Against HIV Infection in the Humanized Mouse Model - Zhen, Anjie (J Vis Exp, 2016)
With the rapid development of stem cell-based gene therapies against HIV, there is pressing requirement for an animal model to study the hematopoietic differentiation and immune function of the genetically modified cells. The humanized Bone-marrow/Liver/Thymus (BLT) mouse model allows for full reconstitution of a human immune system in the periphery, which includes T cells, B cells, NK cells and monocytes. The human thymic implant also allows for thymic selection of T cells in autologous thymic tissue. In addition to the study of HIV infection, the model stands as a powerful tool to study differentiation, development and functionality of cells derived from hematopoietic stem cells (HSCs). Here we outline the construction of humanized non-obese diabetic (NOD)-severe combined immunodeficient (SCID)-common gamma chain knockout (c(γ)(-/-))-Bone-marrow/Liver/Thymus (NSG-BLT) mice with HSCs transduced with CD4 chimeric antigen receptor (CD4CAR) lentivirus vector. We show that the CD4CAR HSCs can successfully differentiate into multiple lineages and have anti-HIV activity. The goal of the study is to demonstrate the use of NSG-BLT mouse model as an in vivo model for engineered immunity against HIV. It is worth noting that, because lentivirus and human tissue is used, experiments and surgeries should be performed in a Class II biosafety cabinet in a Biosafety Level 2 (BSL2) with special precautions (BSL2+) facility.